Determinants of effectiveness of Islamic financial services training / Nurul Hanis Malek - Malek, Nurul Hanis (2014)
The purpose of this study is to identify the main factor that influence the effectiveness of Islamic financial services training and to identify the relationship between (independent variables) which were employees' behavior, training program, social support and effectiveness of Islamic financial services training (dependent variable). For this study, 100 copies of self-administered questionnaires were distributed to the staff of Bank Muamalat Malaysia Berhad who had joined training program which organized by their human resources department. IBM SPSS Statistics 17 was used to analyze and interpret the data collected. The questionnaires were analyzed by using reliability test, descriptive analysis, Multiple Linear Regression and Pearson Correlation. The results showed that training program is the main factor that influences effectiveness of Islamic financial services training and there is positive relationship between the three independent variables and dependent variable. However, there were some limitations and recommendations for this study and were discussed in last chapter.